The Circuit of Culture: A Useful Theoretical Model for Studying Social Media - Keats, Emily Sue (AoIR Selected Papers of Internet Research, 2013)
This theoretical examination illustrates the applicability of the Circuit of Culture to studying social media. Literature that uses the theory of self-presentation for understanding social media and its users abounds. While Goffman’s (1959) presentation of self is an appropriate theoretical approach to the analysis of social media, it focuses primarily on the concept of identity and how users elicit or hide particular aspects of it depending on the self they want to project. Because online environments are multifaceted sites of meaning construction and exchange, examining them with a more diverse and encompassing model is critical. The Circuit of Culture is a five-part model that can be used to provide a rich understanding of a cultural phenomenon. This paper offers evidence for why the Circuit of Culture is a strong model to apply when investigating social media as well as offers suggestions for future research areas.